Soil test crop response nutrient prescription equations for improving soil health and yield sustainability—a long-term study under Alfisols of southern India - Murthy, R. Krishna; Nagaraju, Bhavya; Govinda, K.; Uday Kumar, S. N.; Basavaraja, P. K.; Saqeebulla, H. M.; Gangamrutha, G. V.; Srivastava, Sanjay; Dey, Pradip (Frontiers in Plant Science, 2024)
Introduction Enhancing soil health and nutrient levels through fertilizers boosts agricultural productivity and global food security. However, careful fertilizer use is essential to prevent environmental damage and improve crop yields. The soil test crop response (STCR) is a scientific approach to fertilizer recommendation that ensures efficient use, supporting higher crop production while protecting the environment and preserving resources. Methodology A long-term field experiment on the STCR approach was initiated in 2017 at the Zonal Agriculture Research Station, University of Agricultural Sciences, Bangalore, India. The experiment aimed to study the impact of STCR-based nutrient prescription along with farmyard manure (FYM) for a targeted yield of soybean (Glycine max), sunflower (Helianthus annuus), dry chili (Capsicum annuum), aerobic rice (Oryza sativa L.), foxtail millet (Setaria italica), okra (Abelmoschus esculentus), and kodo millet (Paspalum scrobiculatum) on yield and changes in soil health in comparison with other approaches of fertilizer recommendation. Results The results showed a significant and positive impact of the integrated use of fertilizer with FYM based on the STCR approach on the productivity of all the crops and soil fertility. Significantly higher yields of soybean (23.91 q ha−1), sunflower (27.13 q ha−1), dry chili (16.67 q ha−1), aerobic rice (65.46 q ha−1), foxtail millet (14.07 q ha−1), okra (26.82 t ha−1), and kodo millet (17.10 q ha−1) were observed in the STCR NPK + FYM approach at yield level 1 compared to the general recommended dose and soil fertility rating approach. This approach outperformed the standard recommendations, enhancing nutrient uptake and efficiency across various crops. Utilizing the principal component analysis, the soil quality index effectively reflected the impact of nutrient management on soil properties, with the STCR NPK + FYM treatment at yield level 1 showing the highest correlation with improved soil physical and chemical parameters. Discussion The STCR approach led to improved yield, nutrient uptake, utilization efficiency, and soil health, thanks to a balanced fertilization strategy. This strategy was informed by soil tests and included factors like crop-induced nutrient depletion, baseline soil fertility, the efficiency of inherent and added nutrients through fertilizers and farmyard manure, and the success of yield-targeting techniques in meeting the nutritional needs of crops.